Estudo cinético da pirólise das biomassas: bagaço de mandioca, casca de soja e bagaço de cana - Zanatta, Elciane Regina (2012)
The agro-industries have generated significant amounts of waste, which raises the importance reviewing its destination in the supply chain, being an economic problem, due to waste, it is also a serious environmental problem. These residues also called biomass, due to the insignificant impact on the greenhouse, are an interesting response to the growing demand of renewable energy. Biomass is characterized as a mixture of reference components: cellulose, hemicellulose and lignin. Within this context, the main objective of this study was to investigate the kinetics pyrolysis of biomass: cassava bagasse, soy hulls and sugar cane bagasse. The study was conducted in an inert atmosphere of nitrogen, with temperatures ranging from 60 ° C to 950 ° C for four heating rates: 5, 10, 15, and 20 ° C / min for single-component cellulose, hemicellulose and lignin and temperature ambient to 900 ° C for five heating rates: 5, 10, 15, 20 and 30 ° C / min for biomass. The determination of kinetic parameters was performed using two non-isothermal differential methods: Flynn Wall Ozawa (FWO) and Kissinger. And a full non-isothermal method was used to model the conversion of single components. In the thermal analysis, pyrolysis of hemicellulose and cellulose occurred quickly. The main weight loss of hemicellulose rappened from 208 to 447 ° C and cellulose from 332 to 384 ° C. The lignin was more difficult to decompose, like the weight loss happening in a wide temperature range from 174 to 701 ° C. The weight loss of sugar cane bagasse occurred at temperatures from 270 to 480 ° C, the cassava bagasse from 270 to 540 ° C, and soy hulls from 230 to 560 ° C. The results obtained for activation energy Ea, for the pyrolysis of cellulose, for hemicellulose and lignin are in the range: 132,02 to 161,25 kJ / mol, 39,36 to 77,83 kJ / mol, 54,59 to 735,99 kJ / mol, respectively. The activation energy of biomass pyrolysis of sugar cane bagasse, cassava bagasse and soy hulls are in the range: 126,62 to 148,80 kJ / mol, 157,64 to 227,74 kJ / mol, 140,81 to 195,52 kJ / mol respectively. The results demonstrate how the behavior of decomposition and its kinetic parameters are influenced by the species or type of biomass and by the rate of heating of the process.